Of Incorrect (British Journal of Multidisciplinary and Advanced Studies, 2026)
Impact of incorrect decision is very dangerous. When there is no chance to rectify it the situation goes beyond control. The arrow that is thrown from the bow can never be returned back by any means. It is hard reality. Illegal pregnancy, in the patriarchal society, is the striking example of this kind. The girl commits suicide to save her from shame and social dogma. Such an unfortunate girl has to face honour killing if she is involved with any guy beyond her community or not allowed by her society thereby parents as well. Sometimes parents may agree out of affection but the society, the self-proclaimed guardian never allows thus to protect the so-called chastity of the society.